2015
DOI: 10.1111/ext.12133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Masonry Walls With Flat-Jack Tests

Abstract: The results from an experimental campaign on old masonry buildings from Lisbon are presented and discussed. The tests aim at the evaluation of the masonry deformability properties in compression and the shear strength parameters based on flat-jack testing technique. Tests were carried out in both internal brick masonry walls and external rubble limestone masonry walls. The evaluation of the shear parameters was done according to a new testing technique-shear tests on masonry walls with flat-jacks-involving mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The masonry buildings present an enormous variability in the mechanical properties which reflects the differences between type of material, arrangement and state of conservation. Several works can be found in the literature regarding the mechanical properties of Portuguese masonry building stock (e.g., irregular limestone [26][27][28][29][30][31] ; granite 32,33 ; brick masonry with lime mortar 30,31,[34][35][36] ; brick masonry with cement mortar 13,37 ). Moreover, the latest version of EC8-3 also suggests the mechanical properties for different types of masonry (see Candeias et al 22 ).…”
Section: Materials Properties Definitionmentioning
confidence: 99%
“…The masonry buildings present an enormous variability in the mechanical properties which reflects the differences between type of material, arrangement and state of conservation. Several works can be found in the literature regarding the mechanical properties of Portuguese masonry building stock (e.g., irregular limestone [26][27][28][29][30][31] ; granite 32,33 ; brick masonry with lime mortar 30,31,[34][35][36] ; brick masonry with cement mortar 13,37 ). Moreover, the latest version of EC8-3 also suggests the mechanical properties for different types of masonry (see Candeias et al 22 ).…”
Section: Materials Properties Definitionmentioning
confidence: 99%
“…The use for chaotic and very irregular masonry, on the other hand, raises some questions, and experiments have shown that it can lead to errors in the evaluation of both the modulus of elasticity and compressive strength [90]. Nevertheless, the flat-jack technique has been successfully used in numerous and different stone masonry structures [91][92][93][94][95][96][97][98], proving to be a valid alternative to measure the strain-stress behavior of masonry [85,99,100].…”
Section: Remarks On Double Flat-jack Testsmentioning
confidence: 99%
“…The computation of the compressive strength is still a weak point of the entire analysis procedure, despite the considerable development in recent decades of techniques for their on-site assessment. Besides, there is also a partial lack of literature and standard values, because of the strong heterogeneity of masonry structures in terms of both materials and construction techniques [3][4][5][6][7]. This is relevant for natural stone masonries such as tuff and mortars with different strengths, often altered over time, which are widespread in the Campania region of Italy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Để xác định ứng suất phát sinh trong kết cấu, thông thường, có ba phương pháp được sử dụng: (1) đo trực tiếp thông qua các đầu đo ứng suất (stress gauge); (2) xác định gián tiếp thông qua các đầu đo biến dạng (strain gauge); và (3) xác định gián tiếp thông qua áp suất đo được từ thiết bị đo phụ trợ (ví dụ: flatjack technique -thí nghiệm kích phẳng) [1,2]. Trong đó "kỹ thuật kích phẳng"là một phương pháp đo khá đơn giản và hiệu quả nhằm xác định: (i) ứng suất nén tại hiện trường (in-situ) của các kết cấu khác nhau như đập bê tông [3], vỏ hầm [4]; hoặc (ii) cường độ chịu nén của các vật liệu như gạch [5][6][7][8][9]; đá [10] ... Để đo được ứng suất nén phát sinh trong kết cấu, kỹ thuật này dựa trên nguyên lý cung cấp vào trong kích phẳng một áp suất nhằm cân bằng với ứng suất được giải phóng ra do việc tạo ra một khe cắt mỏng vuông góc với bề mặt chịu lực của kết cấu cần đo. Kỹ thuật kích phẳng có thể coi như là một thí nghiệm không phá hủy vì khe cắt có kích thước khá nhỏ so với kết cấu và sau thí nghiệm chúng ta có thể dễ dàng thu hồi lại được kích phẳng cũng như khôi phục lại kết cấu bằng việc chèn vữa bổ sung vào khe cắt.…”
Section: Giới Thiệuunclassified